The course of fatigue during the development of rheumatoid arthritis and its relation with inflammation: a longitudinal study - Khidir, Sarah J.H. (Joint Bone Spine, 2022)
OBJECTIVE: Fatigue is a prominent and disabling symptom in patients with rheumatoid arthritis (RA), that is only partially explained by inflammation and responds poorly to DMARD-therapy. We hypothesized that inflammation explains fatigue to a larger extent in the phase of clinically suspect arthralgia (CSA), when persistent clinical arthritis is still absent and fatigue has not yet become chronic. We therefore studied the course of fatigue in CSA during progression to RA and the association with inflammation at CSA-onset and at RA-diagnosis. METHODS: 600 consecutive CSA-patients were followed for RA-development. Additionally, 710 early RA-patients were studied at diagnosis. Fatigue was assessed every study visit and expressed on a 0-100 scale. Inflammation was measured with the DAS44-CRP, with and without including subclinical inflammation. The course of fatigue over time was studied with linear mixed models. Associations between fatigue and inflammation were studied with linear regression. Analyses were stratified by ACPA-status. RESULTS: In 88 CSA-patients who developed RA, pre-arthritis fatigue-levels increased gradually with 7 points/year, towards 48 (95%CI=41-55) at RA-development (P=ns). Fatigue decreased in CSA-patients who did not develop RA (4 points/year, P<0.001). At CSA-onset, inflammation was associated with fatigue (β=18, meaning 18 points more fatigue per point increase DAS-score, P<0.01). This association was stronger than at RA-diagnosis (β=5, P<0.001). Fatigue-levels were lower in ACPA-positive pre-RA, but its association with inflammation was stronger compared to ACPA-negative pre-RA. CONCLUSION: Fatigue increased gradually during progression from arthralgia to clinical arthritis, and fatigue was better explained by inflammation in CSA than in RA. This implies a ‘phase-dependent relation’ between inflammation and fatigue.